The Influence Of Leadership Style And Compensation On Employee Performance At The Tasikmalaya District Samsat Office - Yaranova, Andhika Bella; Rahwana, Kusuma Agdhi; Wibawa, Gian Riksa (Utami Publisher, 2024)
This research was conducted to determine the influence of Leadership Style and Compensation on Employee Performance at the Tasikmalaya Regency SAMSAT Office. The research method used was a survey method with a quantitative approach, data was obtained directly through questionnaires distributed to 60 respondents who were SAMSAT employees of Tasikmalaya Regency. The research technique used is multiple linear regression analysis. Based on the research results, it can be seen that Leadership Style and Compensation simultaneously have a significant effect on Employee Performance at the Tasikmalaya Regency SAMSAT Office. Leadership Style partially has a significant effect on Employee Performance at the Tasikmalaya Regency SAMSAT Office, and Compensation partially has a significant effect on Employee Performance at the Tasikmalaya District SAMSAT Office.